PENGARUH GCG, FIRM SIZE, DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - Evangelista Ervandy; Sufiyati Sufiyati (Jurnal Paradigma Akuntansi, 2023)
This study aims to examine the effect of good corporate governance, firm size, and leverage on earning management in manufacture companies listed in Indonesia Stock Exchange (IDX) in 2017-2019. The sample processed using multiple linier regression model in this study amounted to 217 samples. The data in this research were processed using E-views 11.0. The result of this study indicates that board size, firm size, leverage, and institutional ownership have no significant effect on earning management, however auditor size have a negative and significant effect on earning management. The implication of this study is the bigger auditor size, the smaller the probabilitu of earnings management, while board size, firm size, leverage, and institutional ownership does not have a significant effect on earnings management.